IDENTIFICATION OF CRITICAL THINKING CAPABILITIES OF HIGH SCHOOL STUDENTS USING THE INTEGRATED PHYSICS MODULE OF ENGINEERING DESIGN PROCESS (EDP) - Devi Yustika; Pramudya Dwi Aristya Putra; Sri Handono Budi Prastowo (ScienceEdu, 2021)
The Indonesian curriculum states that science education is one of the efforts to improve the quality of people's lives to be able to have knowledge and skills in solving problems. Problem solving skills require capable critical thinking skills to be able to analyze, assess and reconstruct the knowledge they have to solve problems. In addition, the ability to think critically is an important aspect that must be developed according to the competence of 21st-century skills. This research is a type of qualitative research with a case study approach to identify students' critical thinking skills using the Engineering design process (EDP) integrated physics module which is differentiated by gender. The subjects of this study were six students, each consisting of three male students and three female students in class XI MIPA 2 at MAN 1 Jember. The data was collected in the form of observation data, documentation, and interviews. The data collected will be reduced, analyzed based on indicators of critical thinking skills, and presented to then draw conclusions. All data obtained will be tested for validity using triangulation techniques. The results of the identification of critical thinking skills indicate that there are differences in the characteristics of the problem-solving process between male and female students. Female students are better at interpreting problems accurately and in detail than male students. Meanwhile, male students dominate in giving ideas, and even though some ideas are not quite in accordance with the concepts of physics, and are still in doubt. Overall, there is no significant difference between the critical thinking abilities of male and female students. All students tend to still not fully understand the physics concepts related to solutions so that the statements and opinions given regarding solutions tend to be less clear and less logical.